Livestock Manure Type Affects Microbial Community Composition and Assembly During Composting - Wan, Jinxin; Wang, Xiaofang; Yang, Tianjie; Wei, Zhong; Banerjee, Samiran; Friman, Ville-Petri; Mei, Xinlan; Xu, Yangchun; Shen, Qirong (Frontiers in Microbiology, 2021)
Composting is an environmentally friendly way to turn plant and animal wastes into organic fertilizers. However, it is unclear to what extent the source of animal waste products (such as manure) affects the physicochemical and microbiological properties of compost. Here we experimentally tested how the type of livestock manure of herbivores (sheep and cattle) and omnivores (pig and chicken) influences the bacterial and fungal communities and physicochemical properties of compost. Higher pH, NO3-N, Total carbon (TC) content and C/N were found in sheep and cattle manure composts, while higher EC, NH4-N, Total nitrogen (TN) and total phosphorus (TP) content were measured in pig and chicken manure composts. Paired clustering between herbivore and omnivore manure compost metataxonomy composition was also observed at both initial and final phases of composting. Despite this clear clustering, all communities changed drastically during the composting leading to reduced bacterial and fungal diversity and large shifts in community composition and species dominance. While Proteobacteria and Chloroflexi were the major phyla in sheep and cattle manure composts, Firmicutes dominated in pig and chicken manure composts. Together, our results indicate that feeding habits of livestock can determine the biochemical and biological properties of manures, having predictable effects on microbial community composition and assembly during composting. Manure metataxonomy profiles could thus potentially be used to steer and manage composting processes.